Taxonomia e padrões de distribuição dos peixes anostomídeos (Characiformes, Anostomidae) na bacia do Rio Tapajós, Brasil - Feitosa, Francimário da Silva (Instituto Nacional de Pesquisas da Amazônia - INPA, 2011)
Known popularly as aracus or piaus, the fish family Anostomidae (Ostariophysi: Characiformes) are widely distributed throughout South America, from Caribbean island of Trinidad to Argentina (Garavello et al., 1992). The Amazonian basin contains around half of the 140 known species. The present study is a survey of species anostomids in the Tapajós basin, based on analysis of fish collected in upper, middle and low courses of this river and deposited in the collections of INPA and MZUSP. The study area is situated in the northern state of Mato Grosso and western of Pará, part of the "Aquatic Ecoregion Tapajós-Xingu", well known for a large number of waterfalls and rapids and high degree of endemism (Buckup & Santos, 2010). We analyzed 364 specimens of this group of fish collected with different fishing gear and from different locations and types of environment in the study area. The data analysis was based on morphological and meristic taken the aid of calipers and a dissecting microscope, as Garavello (1994) and Santos & Jégu (1996). Were recognized 28 species following, listed in alphabetical order: Anostomoides laticeps, Anostomus ternetzi, Hypomasticus julii, H. pachycheilus, Laemolyta proxima, Leporellus vittatus, Leporinus bistriatus, L. brunneus, Leporinus cf. taeniofasciatus, Leporinus cf. unitaeniatus, L. cylindriformes, L. desmotes, L. falcipinnis, L. friderici, L. maculatus, L. octomaculatus, L. reticulatus, L. sexstriatus, , Leporinus sp. “britskii”, Leporinus sp. “tapaxingus”, L. tigrinus, L. vanzoi, Petulanus intermedius, Pseudanos winterbottomi, Rhytiodus microlepis, Sartor tucuruiense, Schizodon vittatus e Synaptolaemus cingulatus. Diagnoses and key to identification were made, aiming to characterize and facilitate the identification of species. Additionally, we mapped their occurrence and distribuition patterns of trace local and regional. The wildlife of the Tapajós anostomids is the richest among all other watersheds in the Amazon have been investigated. These fish live in different types of environments of the basin, however approximately half the species occurred in areas of rapids and waterfalls. The headwater region showed a high degree of endemism, particularly with smaller species, meaning a high risk of local extinction if these areas will be used to build series of dams, as has been reported on government plans outlined for the region .
Keywords: Peixes; Taxonomia de peixes; Peixes Anastomídeos